2020
DOI: 10.31960/ijolec.v3i1.582
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Matematika Berbasis STEM Pada Materi Bangun Ruang

Abstract: The purpose of this research to develop teaching materials based on Science, Technology, Engineering, and Math (STEM). The type of research is Research and Development (R&D). Meanwhile, the teaching material is developed by ADDIE including five steps, namely analyze, design, development, implementation, and evaluation. The feasibility of the STEM teaching material refers to the results of three expert appraisals, namely education experts, STEM experts, and mathematics experts, then student responses. Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 2 publications
0
5
0
10
Order By: Relevance
“…Jenis penelitian yang dipakai yaitu metode penelitian dan pengembangan (R&D). Mengikuti (Sugiyono, 2019) dalam (Hasanah et al, 2020) mengutarakan bahwa metode penelitian dan pengembangan dipahami bak metode ilmiah untuk meneliti, merancang, melahirkan juga membuktikan efektivitas produk yang dibuat. Untuk itu, tujuan penelitian yaitu membuat suatu produk berupa bahan ajar matematika berbasis matematika terapan yang valid, praktis, dan efektif buat siswa SMK teknik instalasi tenaga listrik pada materi matriks.…”
Section: Metodeunclassified
See 2 more Smart Citations
“…Jenis penelitian yang dipakai yaitu metode penelitian dan pengembangan (R&D). Mengikuti (Sugiyono, 2019) dalam (Hasanah et al, 2020) mengutarakan bahwa metode penelitian dan pengembangan dipahami bak metode ilmiah untuk meneliti, merancang, melahirkan juga membuktikan efektivitas produk yang dibuat. Untuk itu, tujuan penelitian yaitu membuat suatu produk berupa bahan ajar matematika berbasis matematika terapan yang valid, praktis, dan efektif buat siswa SMK teknik instalasi tenaga listrik pada materi matriks.…”
Section: Metodeunclassified
“…Hal itu tidak bagus karena jika guru tidak berimprovisasi dan mengembangkan proses pembelajaran, siswa dapat kehilangan minat pada matematika dan pembelajaran mereka mungkin tidak efektif. Kemudian berdasarkan penelitian yang dilakukan oleh (Hasanah, Wirawati, & Sari, 2020), untuk membuat siswa SMK memahami matematika dengan baik dan mengembangkan diri pada hard skill dan soft skill supaya mereka mampu menyelesaikan masalah yang terjadi pada dunia nyata, maka dilakukan Pengembangan Bahan Ajar Matematika Berbasis STEM Pada Materi Bangun Ruang.…”
unclassified
See 1 more Smart Citation
“…The results showed that the development of STEM-based modules for junior high school students was valid and feasible to use (Zulaiha & Kusuma, 2020). The results also showed that STEM-based teaching materials in building materials met the standards of feasibility aspects and could be used in learning (Hasanah, Mukti, & Aida, 2020). In addition, STEM-based modules on set material were feasible and interesting for students to use (Aminingsih & Izzati, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…STEM is a new approach from a scientific discipline that integrates Science, Technology, Engineering, and Mathematics (Hasanah, Mukti, & Aida, 2020). The STEM approach is an approach that combines more than one field of STEM sciences (Ismayani, 2016).…”
Section: Introductionmentioning
confidence: 99%